Brian [18F]FDG PET associations of cervical cancer-related peripheral inflammatory markers - Hu, Yao; Zhong, Yuan; Hu, Yuxiao (Frontiers in Oncology, 2025)
ObjectiveThe purpose of this study was to explore brain metabolic correlates of peripheral inflammatory markers in patients with cervical cancer (CC).MethodsCervical cancer (CC) patients (267) without treatments who underwent [18F] Fluorodeoxyglucose ([18F]FDG) positron-emission tomography (PET)/computed tomography (CT) were retrospectively studied. All CC patients were grouped into the International Federation of Gynecology and Obstetrics (FIGO) stage II (n=16), the FIGO stage III (n=160), and the FIGO stage IV (n=91) according to the FIGO stage. According to the median of metabolic tumor volume (MTV) or total lesion glycolysis (TLG) for primary tumor in different FIGO stage, CC patients in different FIGO stage were grouped into the Low_MTV (TLG) group (<median) and High_MTV (TLG) group (≥median). Regression analysis were used to explore the relationships between regional brain glucose metabolism and peripheral inflammatory markers [including Neutrophil-to-Lymphocyte ratio (NLR), Platelet-to-Lymphocyte ratio (PLR), Monocyte-to-Lymphocyte ratio (MLR), and systemic immune-inflammation index (SII)] in whole group, subgroups in different FIGO stage.ResultsThe MTV and TLG for primary tumor positively correlated with SII (rMTV=0.402, PMTV=0.000; rTLG=0.397, PTLG=0.000), PLR (rMTV=0.317, PMTV=0.000; rTLG=0.323, PTLG=0.000), NLR (rMTV=0.311, PMTV=0.000; rTLG=0.328, PTLG=0.000), MLR (rMTV=0.255, PMTV=0.001; rTLG=0.275, PTLG=0.000) in FIGO stage III, and they positively correlated with SII (rMTV=0.223, PMTV=0.033; rTLG=0.291, PTLG=0.005), NLR (rTLG=0.220, PTLG=0.036) in FIGO stage IV, but didn’t significantly correlate with MLR, or PLR in FIGO stage IV or with all peripheral inflammatory markers in FIGO stage II (P>0.05). The SII and NLR had significantly negative correlations with the glucose metabolism mainly in the bilateral dorsolateral prefrontal cortex (dlPFC) in CC patients with FIGO stage III (PFWEc< 0.05) and those regions negatively correlated with SII were mainly located in the right dlPFC in CC patients with FIGO stage IV (PFWEc< 0.05). Compared with patients with the Low_MTV (TLG) group in FIGO stage III, those with High_MTV (TLG) group showed stronger relationships between the glucose metabolism of dlPFC and peripheral inflammatory markers (SII, or NLR), while the relationships in FIGO stage IV weakened or even disappeared.ConclusionThe glucose metabolism in the dlPFC negatively correlated with peripheral inflammatory markers in CC patients with FIGO stage III or IV may be relevant in the disease severity and vary depending on the disease severity.